2015
DOI: 10.1371/journal.pone.0120483
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis and Identification of New Isoform of EP4 Receptors in Different Atlantic Salmon Tissues (Salmo salar L.) and Its Role in PGE2 Induced Immunomodulation In Vitro

Abstract: PGE2 plays an important role in a broad spectrum of physiological and pathological processes mediated through a membrane-bound G protein-coupled receptor (GPCR) called EP receptor. In mammals, four subtypes of EP receptor (EP 1-4) are identified and each of them functions through different signal transduction pathways. Orthologous EP receptors have also been identified in other non-mammalian species, such as chicken and zebrafish. EP4 is the only identified PGE2 receptor to date in Atlantic salmon but its tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…In zebrafish, three EP4 genes showed unique expression patterns; and the EP4b transcripts were detected in all tested tissues except for the heart and testis and were highest in the gill [ 33 ]. In our study, we found that PaEP4L mRNA was expressed in all tested tissues with high expression in the intestine and gill, which was similar to that reported in other teleosts [ 19 , 20 ]. In mammals, emerging evidences had shown that chronic inflammation might increase EP4 expression in macrophages [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In zebrafish, three EP4 genes showed unique expression patterns; and the EP4b transcripts were detected in all tested tissues except for the heart and testis and were highest in the gill [ 33 ]. In our study, we found that PaEP4L mRNA was expressed in all tested tissues with high expression in the intestine and gill, which was similar to that reported in other teleosts [ 19 , 20 ]. In mammals, emerging evidences had shown that chronic inflammation might increase EP4 expression in macrophages [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in Atlantic salmon showed that EP4 mRNA expression was highest in the spleen followed by the head kidney, gill and intestine [ 19 , 20 ]. In zebrafish, three EP4 genes showed unique expression patterns; and the EP4b transcripts were detected in all tested tissues except for the heart and testis and were highest in the gill [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations